Kajian Hukum Kesiapan Kampung Adat Anak Rawa Penyengat Dalam Penyelenggaraan Pemerintahan Kampung Di Kabupaten Siak - Jayakusuma, Zulfikar; Davit Rahmadan; Tengku Arif Hidayat (Jurnal Ilmu Hukum, 2025)
Penyengat Village has been designated as a Traditional Village by the Siak Regency Government. The determination carries juridical implications in the form of the necessity of implementing village government based on the customary government system. However, efforts to restore the long-running village government system to the previously abandoned customary government system face various normative and sociological challenges. This study aims to analyze the formulation of the Customary Village policy by the Siak Regency Government and examine the readiness of Penyengat Village as the Original Customary Village of Anak Rawa Penyengat in organizing the government affairs of the Customary Village in Sungai Apit District, Siak Regency. This study uses a normative legal approach supported by empirical data to obtain a comprehensive picture of the implementation of Customary Village policies. The results of the study show that Kampung Penyengat is not fully ready to implement the Traditional Village government. The main obstacles faced include the unresolved boundaries of the village area, community heterogeneity, limited public understanding of the customary government system that has been in effect, low participation of the younger generation, and the lack of optimal socialization of Customary Village policies. In addition, the traditional government system of Kampung Penyengat has different characteristics from the Siak Malay customs, so it requires a deeper arrangement and understanding. Therefore, strategic steps are needed from local governments and indigenous peoples to strengthen institutional aspects, policy socialization, and revitalization of customary values as the basis for the implementation of the Traditional Village government.